Evaluation of the efficacy, safety, and tolerability of BI 409306, a novel phosphodiesterase 9 inhibitor, in cognitive impairment in schizophrenia: a randomized, double-blind, placebo-controlled, phase II trial - Brown, David; Gründer, Gerhard (Schizophrenia bulletin, 2019)
Background: Patients with cognitive impairment associated with schizophrenia may benefit from treatments targeting dysfunctional glutamatergic neurotransmission. BI 409306, a potent and selective phosphodiesterase 9 inhibitor, was assessed in patients with schizophrenia using a learn-and-confirm adaptive trial design. Methods: This double-blind, parallel-group trial randomized patients 2:1:1:1:1 to once-daily placebo or BI 409306 (10, 25, 50, or 100 mg) for 12 weeks. Stage 1 (learn) assessed change from baseline in Cambridge Neuropsychological Test Automated Battery (CANTAB) scores (week 12) to identify ≥1 meaningful endpoints for stage 2 (confirm). If no domains showed efficacy, change from baseline in Measurements and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) Consensus Cognitive Battery (MCCB) composite scores (week 12) was the primary endpoint. The key secondary endpoint was change from baseline in Schizophrenia Cognition Rating Scale (SCoRS) total score. Safety was monitored. Results: Five hundred eighteen patients were randomized. In stage 1, CANTAB did not differentiate between BI 409306 and placebo (n = 120), so the primary endpoint of change from baseline in MCCB composite score was analyzed in 450 patients in stage 2. There was no significant difference between BI 409306 (1.2-2.8) and placebo (2.5) in MCCB composite score change. BI 409306 did not significantly improve change from baseline in SCoRS total score (-3.1 to -2.0) vs placebo (-2.5). Adverse events were dose-dependent, increasing from 33.3% (10 mg) to 53.5% (100 mg), vs 36.4% for placebo. Conclusion: The primary endpoint of cognitive function improvement was not met. BI 409306 was well-tolerated, with an acceptable safety profile.